Neutrophil primary granule proteins HBP and HNP1–3 boost bacterial phagocytosis by human and murine macrophages - Soehnlein, Oliver (American Society for Clinical Investigation, 2008)
In acute inflammation, infiltrating polymorphonuclear leukocytes (also known as PMNs) release preformed granule proteins having multitudinous effects on the surrounding environment. Here we present what we believe to be a novel role for PMN-derived proteins in bacterial phagocytosis by both human and murine macrophages. Exposure of macrophages to PMN secretion markedly enhanced phagocytosis of IgG-opsonized Staphylococcus aureus both in vitro and in murine models in vivo. PMN secretion activated macrophages, resulting in upregulation of the Fcγ receptors CD32 and CD64, which then mediated the enhanced phagocytosis of IgG-opsonized bacteria. The phagocytosis-stimulating activity within the PMN secretion was found to be due to proteins released from PMN primary granules; thorough investigation revealed heparin-binding protein (HBP) and human neutrophil peptides 1–3 (HNP1–3) as the mediators of the macrophage response to PMN secretion. The use of blocking antibodies and knockout mice revealed that HBP acts via β(2) integrins, but the receptor for HNP1–3 remained unclear. Mechanistically, HBP and HNP1–3 triggered macrophage release of TNF-α and IFN-γ, which acted in an autocrine loop to enhance expression of CD32 and CD64 and thereby enhance phagocytosis. Thus, we attribute what may be a novel role for PMN granule proteins in regulating the immune response to bacterial infections.